Ethnobotany of edible plants in Muang District, Kalasin Province, Thailand (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Phatlamphu N, Saensouk S, Saensouk P, Jungsongduang A. 2021. Ethnobotany of edible plants in Muang District, Kalasin Province, Thailand. Biodiversitas 22: 5425- 5431. Edible plants have been used as a food source and have had other purposes since ancient times, but urbanization and modernization might be obscuring traditional knowledge. Therefore, this research aimed to conduct a study on the ethnobotany of indigenous people in Muang District, Kalasin Province based on edible plants by focusing on their specific uses. Data was collected through semi-structured interviews and focus group discussions from March 2019 to February 2021. Quantitative analysis was applied using the Cultural Important Index (CI), Fidelity Level (FL) and Informant Consensus Factor (ICF). Cluster analysis based on the Jaccard’s Similarity Index (JI) was calculated for the similarity of edible plant uses in four communities is as follows: urban/semi-urban (UB), forest community (FC), wetland community (WC) and community in valley (CV). There were 140 edible plant species that belonged to 125 genera and 62 families. The most important edible plants species were Tamarindus indica which had a CI of 2.65 followed by Bambusa bambos (2.00) and Citrus hystrix (1.90). The highest FL value is given for 51 edible plant species with 100% FL. The ICF is a range of 0 to 1; the most consensus of ailment categories was the treatment of wound (ICF = 1.00). The JI varied between 0.2640 and 0.2971; the highest JI was the pairs of WC and FC. UPGMA cluster analysis indicated that UB is isolated as they have less similarity to other communities. The results show a risk of traditional knowledge loss due to the expansion of the economic system at all levels and the advancement of modern medicine.